One-step synthesis of nano-hydroxyapatite/graphene nanosheet hybrid coatings on Ti6Al4V alloys by hydrothermal method and their in-vitro corrosion responses - Yigit, Oktay; Dikici, Burak; Senocak, Taha Cagri; Ozdemir, Niyazi (Elsevier Science Sa, 2020)
The nano-hydroxyapatite (nHA) matrix coatings doped with different graphene nanosheets (GNSs) weight percentages on the Ti6Al4V alloy were synthesized by hydrothermal method, successfully. Surface roughness, porosity, hardness and, in-vitro responses of the coatings have been detailly investigated. The surface morphologies of the nHA/GNS coatings characterized by scanning electron microscope (SEM) and atomic force microscope (AFM). The surfaces crystalline nature and phases of the coating were confirmed by using X-ray diffraction (XRD) and electron dispersive spectroscopy (EDS). An attenuated total reflection infrared (ATR-IR) spectroscopy was used to characterize the functional groups of the coatings. A partially porous structure with nano-scale HA nucleation in the coating was obtained and, the number of nHA nucleation in the layers increased significantly with increasing GNS weight percentage in hybrid structures. The micro Vickers hardness of the hybrid coatings increased with the increasing GNS weight percentage in the coating layer. The electrochemical studies showed that the nHA/GNS hybrid structure progress the in-vitro corrosion resistance of hydrothermal treated Ti6Al4V surfaces. However, there is a certain ratio of GNS in the nHA matrix structure to achieve good surface property. The highest surface area and the high corrosion resistance were obtained in nHA/5GNS coating due to its better surface property than others.
Keywords: Graphene; Hydroxyapatite; Hydrothermal synthesis; Hybrid-coating; Ti6Al4V